The politics of US aid to Pakistan aid allocation and delivery from Truman to Trump - Ali, Murad 1981- (Routledge studies in South Asian politics, 2019)
This book aims at uncovering the politics behind the provision of US foreign aid to Pakistan during three distinctive periods: the Cold War, the post-Cold War and the "war on terror". Focusing on a comprehensive analysis of aid allocation and delivery mechanisms, this book uncovers the primary factors behind historical as well as contemporary US aid to Pakistan so far not thoroughly and empirically studied, especially in the post-2001 period of the "war on terror". Furthermore, based on findings that have emerged from interviews with over 200 respondents, including government officials, representatives of donor aid agencies, the private sector, civil society organizations and primary beneficiaries of US-funded projects, this book offers significant insights to researchers, policy-makers and practitioners interested in the discipline of aid and development effectiveness. Making use of both quantitative and qualitative data and based on extensive fieldwork and primary data, this book fills a significant gap in the empirical analysis of US aid to Pakistan. As such, it will be of great interest to students and scholars of Asian and US politics, as well as to those who have teaching and research interests in disciplines such as international relations, history, strategic studies, international political economy and development studies